ANALISIS KESANTUNAN BERBAHASA MAHASISWA TERHADAP DOSEN UNHASY JOMBANG TEBUIRENG (TINJAUAN PRAGMATIK) - Ramadani Khusnul Khotimah, (Prosiding Seminar Nasioal Pendidikan Bahasa dan Sastra Indonesia (Senapastra), 2024)
Politeness in language is often a problem in the academic world. Morals in language are very important. The problem of politeness or morals in language is often found in conversations between teachers and students and at this time what is often found is among students and lecturers via WhatsApp media or messages in conversations between students and students. Lecturers often make mistakes in using speech that seems less polite and less good, such as using very short sentences and language that is not understood or understood. Incidents like this often and often occur between lecturers' messages to students, even more fatally, students to lecturers. Even though often some lecturers or teachers always give warnings to students to always use polite language and be responsive to the information that has been given with good communication procedures. in WhatsApp groups or messages to lecturers but this is not understood by students or members. This often happens. Methods used to understand phenomena about what research subjects experience, for example behavior, perceptions, motivations, actions. Meanwhile, the approach used in this qualitative descriptive research is a pragmatic approach. The objects of this research are students of the Indonesian Language Education Study Program, FIP, Indonesian Language and Literature Education University, UNHASY Jombang Tebuireng. with a research focus. What is the maxim of praise within the scope of the UNHASY Jombang Tebuireng campus environment? What is the maxim of humility in the UNHASY Jombang Tebuireng campus environment? Then the results of this research are that the maxim of praise within the scope of the UNHASY Jombang Tebuireng campus environment has been implemented very well. The maxim of praise is the habit of praising other people or interlocutors without praising oneself within the scope of the UNHASY Jombang Tebuireng campus. students often do this and have a positive impact on conversations that reduce physical or psychological conflict and then the maxim of humility in the UNHASY Jombang Tebuireng campus environment is to reduce expressions of self-praise; maximize expressions of not praising/exalting yourself. This within the scope of the UNHASY Jombang Tebuireng campus environment is going very well and intensively between lecturers and students